Republic of Korea : Financial Sector Assessment Program-Crisis Preparedness and Crisis Management Framework-Technical Note. (IMF Staff Country Reports; Country Report, 2015)
Korea experienced significant financial distress in the late 1990s along with some of its Asian neighbors. The authorities' experience in handling this crisis and the experience in handling the fallout from the global financial crisis in 2007-08 helped them establish a broad crisis management framework in Korea. Improving and formalizing the framework for crisis management would help preserve and build upon institutional memory. Authorities can consider formally setting up an apex forum for leading the inter-agency cooperation and coordination work on crisis preparedness and crisis management. With a view to avoid duplication, the authorities may consider upgrading the Macroeconomic Financial Meeting (MEFM) with participation by the heads of the Ministry of Strategy and Finance (MOSF), Financial Services Commission (FSC), Financial Supervisory Service (FSS), Bank of Korea (BOK), and Korea Deposit Insurance Corporation (KDIC) as members, and by including crisis preparedness and crisis management as an explicit mandate. The essential elements of a financial safety net are available in Korea, and the Emergency Liquidity Assistance (ELA) framework and deposit insurance system can be improved to make the safety net more responsive. For ELA, this can be achieved by reviewing and revising the legal and procedural aspects to remove any scope for delays in actual disbursement of funds. For deposit insurance system, improvements can be made by bringing the deposit insurance fund out of deficit, and assuring a back-up funding. The financial safety net is well supported by an efficient framework of financial sector supervision. While the corrective action framework has some of the main elements in place it can, among others, be improved in the following areas for better effectiveness: (a) reviewing the triggers for corrective actions and improving their objectivity to enable timely intervention, including even before banks breach regulatory thresholds; and (b) putting in place norms and guidance determining the use of the powers to postpone or suspend corrective actions.